TRENDS IN IMPROVING THE INVESTMENT CLIMATE AND DEVELOPING ECONOMIC GROWTH STRATEGIES IN COUNTRIES - Berdikulova Sevinch Tokhir qizi; Ismoilova Intizor Mansurbek qizi (Western European Studies, 2025)
This article analyzes the impact of investments on economic growth, mechanisms for attracting them, and current problems in this process. The article provides recommendations for developing public-private partnerships to attract investments, creating a favorable business environment, and ensuring economic stability.
Keywords: Investments; regulation; diversification